Pelatihan Manajemen Antrian untuk Meningkatkan Efisiensi Pelayanan di Puskesmas Saitnihuta: Queue Management Training to Improve Service Efficiency at Saitnihuta Community Health Center - Gaol, Crisna Lumban; Hutagaol, Dewi A. L.; Siboro, Kino (Chakra Brahmanda Lentera Institute, 2025)
Queue management is a common challenge faced by primary healthcare facilities such as community health centers (Puskesmas), leading to prolonged patient waiting times and low service satisfaction. One solution to improve service efficiency is through queue management training for healthcare workers and administrative staff. The aim of this community service activity was to enhance understanding and skills in managing queuing systems to create a more structured and responsive service flow that meets patient needs. This community engagement activity utilized a participatory-educational approach and was conducted at Saitnihuta Public Health Center, Doloksanggul Subdistrict, Humbang Hasundutan Regency. The implementation methods included initial observations, training module development, interactive discussions, and hands-on simulations of queue system implementation. A total of 26 participants, consisting of medical personnel and administrative staff, took part in the training. Evaluation was conducted through pre- and post-tests, as well as satisfaction surveys to assess the effectiveness of the training. The results showed that all participants completed the training and actively engaged in the activities. Participants were able to understand the basic concepts of queue management, identify effective management strategies, and demonstrated enthusiasm in implementing changes such as separating service flows and utilizing simple queueing technologies. There was a notable improvement in both understanding and readiness to implement more efficient queuing strategies. The queue management training successfully improved participants’ knowledge and awareness of the importance of effective queue management. It is recommended that similar training be conducted regularly and accompanied by follow-up mentoring to ensure the sustainability of efficient and patient-friendly service systems.